Transforming Madrasah Education: Integrating Technology, Governance, and Commitment within Management Information Systems - Syamsul Bahri; Satriani Satriani; Muhammad Hasbi (Dirasah International Journal of Islamic Studies, 2026)
In the digital age, madrasah education transformation is often impeded by inadequate management information systems (MIS), resulting from disjointed technology integration, ineffective governance, and insufficient organizational commitment. This study analyzes how technology integration, governance, and organizational commitment drive madrasah education transformation to strengthen MIS effectiveness. Using a quantitative approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS) on a sample of teachers in Makassar City, the study identifies education transformation as a central mediator. The findings reveal that technology integration (0.452) and governance (0.351) are the most dominant direct determinants of MIS effectiveness. Organizational commitment does not have a significant direct effect on MIS (p = 0.381). Still, it does have a significant indirect effect through a full mediation mechanism via education transformation, which is shown by changes in digital culture and new curriculum ideas. The structural model demonstrates excellent predictive power, explaining 76.3% of the variation in education transformation and 63.8% of the variation in MIS effectiveness. This research underscores that successful digitalization depends not only on technical readiness but also on the institution's ability to internalize technology through a comprehensive work culture transformation.